A short history of SLA: Where have we come from and where are we going?. (April 2021) - Ellis, Rod
Abstract : If we want to understand where we are now, we need to consider where we have come from. This statement constitutes the strongest rationale for the study of history. It is relevant to any field of enquiry and it is certainly true of the field of second language acquisition (SLA). As Larsen-Freeman (2018) wrote in her own historical account of SLA 'it is important to understand ideas at the time they originated' (p. 56). I would add that it is also important to understand how the ideas that motivated a field of enquiry at one time evolved into and were sometimes replaced by ideas later on.